Positive electrode material and preparation method thereof, positive plate, sodium ion battery and electric equipment
By adding Y and Ca elements to the positive electrode material of sodium ion battery and adjusting the structure and process, the problem of poor electrochemical performance of materials in sodium ion battery is solved, high rate performance and long cycle stability are achieved, and battery life is extended.
Patent Information
- Application Number
- CN202411254421.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
Laminated oxide polycrystalline materials in sodium ion batteries have disordered crystal growth direction and complex diffusion paths of sodium ions, resulting in poor electrochemical performance and unstable structural effects, affecting the rate performance and cycle life of the battery.
By adding specific amounts of Y and Ca elements to the positive electrode material, the microstructure of the material is adjusted, so that the primary particles are refined into rod-shaped, and the secondary particles are arranged radially, exposing more (010) crystal planes, and increasing the Na+ diffusion rate. And optimize material properties by at least two heat treatment and crushing screening processes.
It significantly improves the rate performance and cycling performance of the material, enhances structural stability, extends the service life of the battery, and simplifies the preparation process.
Smart Images

Figure CN119133432A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of positive electrode materials for sodium ion batteries, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet, a sodium ion battery and an electrical device. Background Art
[0002] As energy demand continues to grow and environmental awareness increases, it is urgent to develop high-performance, sustainable energy storage technologies. Among the many energy storage technologies, sodium-ion batteries have gradually become a research hotspot due to their advantages such as abundant sodium resources and relatively low cost.
[0003] Among the key components of sodium-ion batteries, cathode materials are of vital importance. Although layered oxide polycrystalline materials are potential cathode materials for sodium-ion batteries, they face severe challenges.
[0004] The disordered crystal growth direction is a prominent problem. The lack of a specific growth orientation results in poor regularity of the crystal structure, which not only affects the electrical properties of the material, but also makes the diffusion path of sodium ions in the material complex and tortuous. Therefore, the poor diffusion performance of sodium ions has become a key factor restricting the application of layered oxide polycrystalline materials. The slow diffusion rate of sodium ions leads to low ion transfer efficiency and poor rate performance during battery charging and discharging. Moreover, after multiple charge and discharge cycles, the material structure is prone to irreversible changes, such as phase change and lattice collapse, which causes the battery capacity to decay rapidly and shortens the battery life.
[0005] To solve these problems, researchers have been working hard to explore new synthesis methods, improve material structure design, and optimize preparation processes. For example, in the preparation of layered oxide polycrystalline materials, although the high specific surface area of the particles provides more reaction sites, there are grain boundaries inside, and sodium ions diffuse slowly through the grain boundaries. In addition, the self-assembled particle configuration makes the internal diffusion to the external channel tortuous, and the material rate performance is still poor. Another example is the preparation of layered oxide single crystal materials. Although the lattice arrangement inside the particles is orderly and the sodium ions diffuse quickly, the conventional particle size is large, the sodium ion diffusion path is long, and the internal stress generated by the volume change during charging and discharging will cause the material to break during the cycle, causing new problems.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The first object of the present invention is to provide a positive electrode material, by adding a specific amount of Y and Ca elements, to improve the structural stability and increase the Na + The diffusion rate is greatly improved, thereby greatly improving the rate performance and cycle performance of the material.
[0008] The second object of the present invention is to provide a method for preparing a positive electrode material, which has the advantages of simple operation, short process, and excellent electrochemical properties of the prepared material.
[0009] The third object of the present invention is to provide a positive electrode sheet having excellent electrochemical performance, high rate performance and long cycle stability.
[0010] A fourth object of the present invention is to provide a sodium ion battery having the advantages of high rate performance, good cycle stability, and low cost.
[0011] A fifth object of the present invention is to provide an electrical device.
[0012] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0013] The present invention first provides a positive electrode material, the general formula of which is Na i (Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 1-x- y Y x Ca y O2;
[0014] Among them, 1≤i≤1.1, 0.001≤x≤0.02, 0.001≤y≤0.05, and 0.25≤x / y≤0.6.
[0015] Furthermore, the positive electrode material is an O3 phase layered oxide material.
[0016] Furthermore, the positive electrode material is a polycrystalline material.
[0017] Furthermore, the positive electrode material includes spherical secondary particles formed by radially arranging and stacking rod-shaped primary particles.
[0018] Furthermore, the primary particles of the positive electrode material expose 010 crystal planes, and the area of the 010 crystal planes accounts for 45% to 65%.
[0019] The present invention further provides a method for preparing the positive electrode material, comprising the following steps: uniformly mixing a nickel-iron-manganese precursor, a sodium source, a Y-containing compound and a Ca-containing compound, and then performing at least two heat treatments.
[0020] Furthermore, the nickel-iron-manganese precursor includes Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 and / or Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.
[0021] Furthermore, the Y-containing compound includes at least one of Y2O3 and Y2(CO3)3.
[0022] Furthermore, the Ca-containing compound includes at least one of CaO, CaCO3 and Ca(OH)2.
[0023] Furthermore, the temperature of each heat treatment is 850-1050° C., and the time of each heat treatment is 10-30 hours.
[0024] Furthermore, after each heat treatment, crushing and screening are performed.
[0025] The present invention further provides a positive electrode sheet, comprising the positive electrode material.
[0026] The present invention further provides a sodium ion battery, comprising the positive electrode sheet.
[0027] The present invention also provides an electrical device, comprising the sodium ion battery.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The present invention adds a specific amount of Y and Ca elements to refine the primary particles into rods, and the secondary particles are more regular radial, which can expose more (010) crystal planes, thereby improving the Na + The diffusion rate has greatly improved the rate performance and cycle performance of the material, and enhanced the structural stability of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 This is a SEM image of the positive electrode material prepared in Example 1 provided by the present invention;
[0032] Figure 2 This is a SEM image of the positive electrode material prepared in Example 2 provided by the present invention;
[0033] Figure 3 This is a SEM image of the positive electrode material prepared in Comparative Example 1 provided by the present invention;
[0034] Figure 4 This is a SEM image of the positive electrode material prepared in Comparative Example 2 provided by the present invention. DETAILED DESCRIPTION
[0035] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0036] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0037] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0038] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.
[0039] In a first aspect, the present invention provides a positive electrode material, the general formula of the positive electrode material is Na i (Ni 1 / 3 Fe 1 / 3Mn 1 / 3 ) 1-x-y Y x Ca yO2; wherein 1≤i≤1.1, 0.001≤x≤0.02, 0.001≤y≤0.05, and 0.25≤x / y≤0.6. wherein i includes but is not limited to any point value of 1, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.1, or any range value between two of them; x includes but is not limited to any point value of 0.001, 0.003, 0.005, 0.008, 0.01, 0.011, 0.012, 0.013, 0.015, 0.016, 0.018, or any range value between two of them; y includes but is not limited to any point value of 0.001, 0.003, 0.005, 0.008, 0.01, 0.011, 0.012, 0.01 3, 0.015, 0.016, 0.018, 0.02, 0.023, 0.025, 0.028, 0.03, 0.032, 0.035, 0.038, 0.04, 0.043, 0.045, 0.047, 0.05, or any range between two of them; the ratio x / y includes but is not limited to 0.25, 0.26, 0.28, 0.3, 0.33, 0.35, 0.38, 0.4, 0.43, 0.45, 0.47, 0.5, 0.52, 0.55, 0.58, 0.6, or any range between two of them.
[0040] The present invention achieves significant improvement on the microstructure and performance of the material by adding specific amounts of two elements, Y and Ca, into the layered oxide positive electrode material.
[0041] Specifically, after adding a specific amount of Y and Ca, the originally disorderly growing polycrystalline primary particles were refined. The original small flake particles were transformed into rod-shaped particles, and the overall secondary particles were more regular radial. Without changing the type of crystal, this structural change caused the crystal to expose more (010) faces. This change is of great significance because more (010) face exposure increases the Na + diffusion channel, thus significantly increasing the Na + Diffusion rate. + The increase in diffusion rate has greatly improved the rate performance and cycle performance of the material. After multiple charge and discharge cycles, the structural stability of the material is enhanced and the capacity decay is effectively suppressed.
[0042] Therefore, the positive electrode material with a specific chemical composition provided by the present invention has good structural stability and excellent rate performance and cycle performance.
[0043] In some specific embodiments, the positive electrode material is an O3 phase layered oxide material.
[0044] In some specific embodiments, the positive electrode material is a polycrystalline material.
[0045] In some specific embodiments, the positive electrode material includes spherical (or quasi-spherical) secondary particles formed by radially arranging and stacking rod-shaped primary particles, see Figure 1 and Figure 2 As shown. That is, the shape of the primary particles is rod-shaped, and the shape of the secondary particles is spherical or quasi-spherical. The interior (cross section) of the secondary particles is arranged radially from the center to the surface.
[0046] In some specific embodiments, the primary particles of the positive electrode material expose a 010 crystal plane, see Figure 1 and Figure 2 As shown, the area proportion of the 010 crystal plane is 45% to 65%, including but not limited to any point value of 45%, 48%, 50%, 53%, 55%, 57%, 60%, 62%, 65% or the range value between any two of them.
[0047] In a second aspect, the present invention provides a method for preparing the positive electrode material, which specifically comprises the following steps: uniformly mixing a nickel-iron-manganese precursor, a sodium source, a Y-containing compound and a Ca-containing compound according to a target chemical formula ratio, performing at least two heat treatments, and then cooling to obtain the positive electrode material.
[0048] At least two heat treatments can make the sodium element more evenly distributed and the reaction more complete.
[0049] The present invention provides a method for preparing the positive electrode material, which has simple operation, short process, and excellent electrochemical performance of the prepared material, and is suitable for mass production.
[0050] In some specific embodiments, the nickel-iron-manganese precursor includes Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 and / or Ni 1 / 3Fe 1 / 3 Mn 1 / 3 O2.
[0051] In some specific embodiments, the Y-containing compound includes at least one of Y2O3 and Y2(CO3)3.
[0052] In some specific embodiments, the Ca-containing compound includes at least one of CaO, CaCO3 and Ca(OH)2.
[0053] In some specific embodiments, the sodium source includes any compound containing sodium, such as sodium carbonate, but not limited thereto.
[0054] In some specific embodiments, the temperature of each heat treatment is 850-1050°C, including but not limited to any point value of 850°C, 880°C, 900°C, 930°C, 950°C, 980°C, 1000°C, 1030°C, 1050°C or the range value between any two of them.
[0055] In some specific embodiments, the holding time for each heat treatment is 10 to 30 hours, including but not limited to any one of 10 hours, 12 hours, 15 hours, 18 hours, 20 hours, 22 hours, 24 hours, 26 hours, 28 hours, and 30 hours, or a range between any two of them.
[0056] In some specific embodiments, after each heat treatment, crushing and screening are performed.
[0057] In some specific embodiments, the heat treatment can be performed in any heating setting commonly used in the art, such as a high temperature furnace, but is not limited thereto.
[0058] In a third aspect, the present invention provides a positive electrode sheet comprising the positive electrode material.
[0059] The positive electrode sheet has excellent electrochemical performance, high rate performance and long cycle stability.
[0060] Optionally, the positive electrode sheet further includes a binder and / or a conductive agent, which is not limited in the present invention.
[0061] In a fourth aspect, the present invention provides a sodium ion battery comprising the positive electrode sheet.
[0062] The sodium ion battery has the advantages of high rate performance, good cycle stability and low cost.
[0063] Optionally, the sodium ion battery further comprises a negative electrode sheet, a separator and an electrolyte, which is not limited in the present invention.
[0064] In a fifth aspect, the present invention provides an electrical device comprising the sodium ion battery.
[0065] The sodium ion battery provided by the present invention can be widely used in various fields and made into various electrical equipment, devices or systems.
[0066] As examples, the electrical equipment includes electric vehicles, electric motorcycles, electric bicycles, electric tools, starting power supplies, energy storage devices, electronic products, and office equipment, but is not limited thereto.
[0067] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0068] Example 1
[0069] The Na provided in this embodiment 1.042 (Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 0.944 Y 0.014 Ca 0.042 The preparation method of the positive electrode material of O2 sodium ion battery comprises the following steps: weighing 1000.0 g of Na2CO3, Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 1562.3g (OH)2, 28.9g Y2O3, and 43.0g CaO were mixed evenly, loaded into a ceramic crucible, placed in a muffle furnace, and heat treated three times according to the following conditions: the first heat treatment temperature was 850℃, and the heat preservation time was 30h; the second heat treatment temperature was 980℃, and the heat preservation time was 15h; the third heat treatment temperature was 1000℃, and the heat preservation time was 12h. After each heat treatment, it was crushed and sieved. After the heat treatment was completed, it was cooled to obtain the positive electrode material.
[0070] Example 2-Example 6
[0071] Referring to the preparation method of Example 1, the amount of raw materials and the heat treatment conditions were adjusted to obtain positive electrode materials with different compositions. The specific differences are shown in Table 1 and Table 2.
[0072] Table 1 Chemical formula of positive electrode materials and the amount of each raw material, as well as the value of x / y
[0073]
[0074] Table 2 Heat treatment conditions
[0075]
[0076] Comparative Example 1-Comparative Example 7
[0077] Referring to the preparation method of Example 1, the amount of raw materials and the heat treatment conditions were adjusted to obtain positive electrode materials with different compositions. The specific differences are shown in Tables 3 and 4.
[0078] Table 3 Chemical formula of positive electrode materials and the amount of each raw material, as well as the value of x / y
[0079]
[0080] Table 4 Heat treatment conditions
[0081]
[0082]
[0083] Experimental Example 1
[0084] EBSD test: After the cathode material is processed into a suitable state and the surface is polished, the cathode material is placed on the EBSD sample stage of the scanning electron microscope and the equipment is turned on to set the parameters. The scan is started, the electron beam scans the sample, and the detector collects and stores the data. The data is then processed using software to obtain the area ratio of the 010 crystal plane, as shown in Table 5.
[0085] Table 5 Area ratio of 010 crystal face in primary particles of positive electrode materials
[0086] Group 010 crystal surface area ratio Example 1 59.66% Example 2 63.94% Example 3 57.05% Example 4 48.67% Example 5 54.62% Example 6 53.02% Comparative Example 1 41.68% Comparative Example 2 27.60% Comparative Example 3 44.38% Comparative Example 4 29.11% Comparative Example 5 33.52% Comparative Example 6 33.18% Comparative Example 7 29.31% Comparative Example 8 34.36%
[0087] Experimental Example 2
[0088] The positive electrode materials prepared in each embodiment and each comparative example were used as active materials to prepare positive electrode sheets and sodium ion batteries according to the following method:
[0089] Preparation of button cells: The positive electrode materials prepared in each embodiment and each comparative example were placed at a constant humidity of 50% for 30 minutes, and then as active materials, 0.45g of active material, 0.025g of SP (SP is specifically Swiss SUPER P high-conductive carbon black) and 0.25g of polyvinylidene fluoride glue (mass percentage 10%, solute is SOLVAY PVDF5130, solvent is NMP) were uniformly mixed, and then NMP was added to make a viscous glue. The glue was coated on an aluminum foil with a thickness of 16μm, and then baked in a vacuum drying oven at 120℃ for 12h to obtain a positive electrode sheet with an active material surface density of 5mg / cm 2. A 300μm thick sodium metal sheet (Aladdin) was used as the counter electrode, a 675μm thick glass fiber (Waterman) was used as the diaphragm, and a 1mol / L NaPF6 solution (the solvent was a mixture of EC and DMC in a volume ratio of 1:1) was used as the electrolyte. A 2032 button cell was assembled in an Ar atmosphere protection glove box. Afterwards, at 25°C, each battery was charged to 4.0V at a constant current of 0.1C (nominal specific capacity 100mAh / g), and then charged at a constant voltage until the current was less than or equal to 0.01mA, then left to stand for 5 minutes, and then discharged to 2.5V at a constant current of 0.1C. This was the activation process of the battery, and subsequent tests were performed after activation.
[0090] The test method of electrochemical performance is as follows: (1) At 25°C, charge the battery to 4.0V at a constant current of 0.5C, then charge at a constant voltage until the current is less than or equal to 0.01mA, then let it stand for 5 minutes, and then discharge to 2.5V at a constant current of 0.5C, then let it stand for 5 minutes. This is a charge and discharge cycle, and the discharge capacity is recorded as the discharge capacity of the first cycle at a charge and discharge rate of 0.5C. The battery is charged and discharged 100 times according to the above method, and the discharge capacity of the 100th cycle is recorded. Then, the discharge capacity of the 100th cycle / the discharge capacity of the first cycle × 100% is the cycle retention rate. (2) At 25°C, charge the battery to 4.0V at a constant current of 0.5C, then charge at a constant voltage until the current is less than or equal to 0.01mA, then let it stand for 5 minutes, and then discharge it to 2.5V at a constant current of 0.5C, then let it stand for 5 minutes. This is a charge and discharge cycle. The discharge capacity is recorded as the discharge capacity at a charge and discharge rate of 0.5C. The battery was modified to 1C and 2C according to the above method for charge and discharge tests, and the discharge capacity was recorded to obtain the discharge capacity at different charge and discharge rates. The electrochemical performance test results are shown in Table 6.
[0091] Table 6 Electrochemical performance test results
[0092]
[0093] It can be seen from Table 6 that the positive electrode materials prepared in each embodiment have excellent rate performance and cycle performance. However, in each comparative example, since no Y or Ca is added or the ratio of Y to Ca is not appropriate, the rate performance or cycle performance is reduced.
[0094] It can be seen that the positive electrode material with a specific chemical composition provided by the present invention can significantly improve the microstructure and electrochemical performance of the material by adding specific amounts of two elements, Y and Ca.
[0095] In addition, if Figure 1 The SEM image of the positive electrode material prepared in Example 1 provided by the present invention is shown; Figure 2 The SEM image of the positive electrode material prepared in Example 2 provided by the present invention is shown; Figure 3 The SEM image of the positive electrode material prepared in Comparative Example 1 provided by the present invention is shown; Figure 4 The SEM image of the positive electrode material prepared in Comparative Example 2 provided by the present invention is shown. Figure 1 and Figure 2 As shown, the lamella interface is in the 010 direction.
[0096] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A positive electrode material, characterized in that: The general formula of the positive electrode material is Na i (Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 1-x-y Y x Ca y O2; Among them, 1≤i≤1.1, 0.001≤x≤0.02, 0.001≤y≤0.05, and 0.25≤x / y≤0.
6.
2. The positive electrode material according to claim 1, characterized in that: At least one of the following conditions is met: (1) The positive electrode material is an O3 phase layered oxide material; (2) The positive electrode material is a polycrystalline material.
3. The positive electrode material according to claim 1, characterized in that: At least one of the following conditions is met: (1) The positive electrode material comprises spherical secondary particles formed by radially arranging and stacking rod-shaped primary particles; (2) The primary particles of the positive electrode material expose 010 crystal planes, and the area ratio of the 010 crystal planes is 45% to 65%.
4. The method for preparing the positive electrode material according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: uniformly mixing a nickel-iron-manganese precursor, a sodium source, a Y-containing compound and a Ca-containing compound, and then performing heat treatment at least twice.
5. The method for preparing the positive electrode material according to claim 4, characterized in that: At least one of the following conditions is met: (1) The nickel-iron-manganese precursor comprises Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 and / or Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2; (2) the Y-containing compound comprises at least one of Y2O3 and Y2(CO3)3; (3) The Ca-containing compound includes at least one of CaO, CaCO3 and Ca(OH)2.
6. The method for preparing the positive electrode material according to claim 4, characterized in that: The temperature of each heat treatment is 850-1050° C., and the time of each heat treatment is 10-30 hours.
7. The method for preparing the positive electrode material according to claim 4, characterized in that: After each of the heat treatments, crushing and screening are performed.
8. A positive electrode sheet, characterized in that: The positive electrode material comprises the positive electrode material as claimed in any one of claims 1 to 3.
9. A sodium ion battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 8.
10. An electrical device, characterized in that: Comprising the sodium ion battery as claimed in claim 9.
